Adjusting photocatalytic hydrogen production of TiO2 hollow nanospheres through nitrogen-induced shallow trapping levels - Qingmiao Ren; Peng Chen; Na Sun; Miao Yue; Qi Zhang; Weihu Kong; Gaofei Ren; Wen Guo; Yongming Fu; Jie Ma (Journal of Advanced Dielectrics)
N-doped titanium dioxide (TiO[Formula: see text] hollow nanospheres with abundant oxygen vacancies were successfully synthesized by coupling urea treatment and annealing in an N2 atmosphere. The pristine TiO2 hollow nanospheres exhibit a shallow donor level for electron trapping, while the urea treatment generates a N 2p acceptor level for hole trapping. After annealing in N2, the sufficient N atoms generate abundant oxygen vacancies for trapping electrons, resulting in further improved charge separation efficiency. The N-doped TiO2 exhibits the highest H2 evolution rate, reaching 2867[Formula: see text][Formula: see text]mol[Formula: see text]g[Formula: see text][Formula: see text]h[Formula: see text], which is six times higher than that of pristine TiO2 hollow nanospheres. The introduction of oxygen vacancies by interstitial N provides a promising way to improve the photocatalysis activity of photocatalysts.